Discovery of SARS-CoV-2 inhibitors featuring novel histidine α-nitrile motif - Gone, Nilu Vijay; Enayathullah, Mohammed Ghalib; Thomas, Jessie; Rathee, Parth; Prabhakar, Rajeev; Bokara, Kiran Kumar; Sanjayan, Gangadhar J. (Chemistry and Biodiversity, 2023)
As COVID-19 infection caused severe public health concerns recently, the development of novel antivirals has become the need of the hour. Main protease (Mpro) has been an attractive target for antiviral drugs since it plays a vital role in polyprotein processing and virus maturation. Herein we report the discovery of a novel class of inhibitors against the SARS-CoV-2, bearing histidine alpha-nitrile motif embedded on a simple dipeptide framework. In-vitro and in-silico studies revealed that the histidine alpha-nitrile motif envisioned to target the Mpro contributes to the inhibitory activity. Among a series of dipeptides synthesized featuring this novel structural motif, some dipeptides displayed strong viral reduction (EC50=0.48 mu M) with a high selectivity index, SI>454.54. These compounds also exhibit strong binding energies in the range of -28.7 to -34.2 Kcal/mol. The simple dipeptide structural framework, amenable to quick structural variations, coupled with ease of synthesis from readily available commercial starting materials are the major attractive features of this novel class of SARS-CoV-2 inhibitors. The histidine alpha-nitrile dipeptides raise the hope of discovering potent drug candidates based on this motif to fight the dreaded SARS-CoV-2.
Keywords: dipeptide inhibitors; histidine alpha-nitrile; M-pro (main protease); molecular dynamics; SARS-CoV-2

Repurposed ciprofloxacin derivatives as potent autophagic-type anticancer agents - Gone, Nilu Vijay; Sharma, Tanisha; Joshi, Rakesh; Upreti, Akshita; Santra, Manas; Sanjayan, Gangadhar J. (Bioorganic & Medicinal Chemistry Letters, 2026)
Drug repurposing - also known as drug repositioning is a proven strategy for identifying new therapeutic uses for existing and pre-approved drugs with considerable success in recent years. Herein, we report the discovery of a novel class of ciprofloxacin-amino acid conjugates that are dynamically potent against different cancer cell lines. Some of the molecules reported herein displayed a strong anti-proliferative effect on MCF-7 (IC50: 6 mu M). The most active anti-proliferative molecule of this series 7a suppressed the proliferation of HCT116, A549, and MDAMB-231 cancer cell lines. Furthermore, we established that the treatment with 7a leads to DNA damage-mediated autophagic cell death in cancer cells. Our findings suggest that appropriate derivatization of the ciprofloxacin drug can yield promising anti-cancer compounds in easy synthetic operations.
Keywords: Anticancer drugs; Autophagic cell death; ciprofloxacin